The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00018-018-2955-0
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid exposure during pregnancy and its impact on immune function

Abstract: Cannabinoids are the most commonly abused illicit drugs worldwide. While cannabis can be beneficial for certain heath conditions, abuse of potent synthetic cannabinoids has been on the rise. Exposure to cannabinoids is also prevalent in women of child-bearing age and pregnant women. These compounds can cross the placental barrier and directly affect the fetus. They mediate their effects primarily through G-protein coupled cannabinoid receptors, CB1 and CB2. In addition to significant neurological effects, cann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 171 publications
(203 reference statements)
0
48
0
2
Order By: Relevance
“…Cannabinoids are known to interact with the immune system at multiple points including CB1 and CB2 receptors, six vanilloid channels, peroxisome proliferator-activated receptors (PPAR's), serotonin, adenosine, histamine, glycine, sphingosine, dopamine and opioid receptors, three class A orphan G-protein coupled receptors (GPCR's), toll-like receptors, Tcells, B-cells, macrophages and regulatory cells, effects on sodium channels and several types of potassium and calcium channels, modulation of GABA signalling and inhibition of cyclooxygenase and lipoxygenase enzymes, bind directly to mitochondria and cannabinoid receptors also form heterodimers with opioid, adenosine, dopamine, GABA and other GPCR's and have myriad and major epigenetic effects [13][14][15][16][17][18][19][20][33][34][35][36][37][38] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cannabinoids are known to interact with the immune system at multiple points including CB1 and CB2 receptors, six vanilloid channels, peroxisome proliferator-activated receptors (PPAR's), serotonin, adenosine, histamine, glycine, sphingosine, dopamine and opioid receptors, three class A orphan G-protein coupled receptors (GPCR's), toll-like receptors, Tcells, B-cells, macrophages and regulatory cells, effects on sodium channels and several types of potassium and calcium channels, modulation of GABA signalling and inhibition of cyclooxygenase and lipoxygenase enzymes, bind directly to mitochondria and cannabinoid receptors also form heterodimers with opioid, adenosine, dopamine, GABA and other GPCR's and have myriad and major epigenetic effects [13][14][15][16][17][18][19][20][33][34][35][36][37][38] .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly the cannabis industry is known to have recently increased its activity significantly in USA following widespread relaxation of regulations pertaining to its use, and a 2018 study indicated that legalization was associated with an increase of more than 1,000,000 cannabis users and 500,000 cannabis-dependent people 11 . A large literature describes the immunosuppressive properties of several cannabinoids including Δ9tetrahydrocannabinol (THC), cannabidiol and cannabinol [12][13][14][15][16][17][18][19][20] . Cannabis users frequently inhale with deep breaths which are held for long period so that smoke can penetrate deeply into the lung 12,21 .…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…In the context of increasing marijuana use among pregnant women, 2,6 it is clear that more studies on the relationship between prenatal cannabis exposure and offspring developmental outcomes are needed to examine potential causal effects, moderating or protective factors, and biological mechanisms at play. 69,70 Similar to the highly effective messaging surrounding the adverse consequences of alcohol and tobacco exposure during pregnancy, education regarding the potential harms associated with prenatal marijuana use is necessary. Currently, cannabis use during pregnancy should be discouraged by care providers and dispensaries.…”
Section: Discussionmentioning
confidence: 99%
“…Given the increased prevalence of cannabis use in the U.S., studies are beginning to focus on the effects of use on the health and development of offspring. Prenatal cannabis exposure via maternal use during pregnancy is associated with decreased infant birth weight, an increased likelihood to require the neonatal intensive care unit, and the potential for an impaired fetal immune system compared to those infants who are not exposed during gestation [1,12]. In rodent studies, rat pups born to parents who were both exposed to THC during adolescence had increased heroin-seeking behaviour later in life, a phenotype that was accompanied by epigenetic changes in the nucleus accumbens [13][14][15].…”
Section: Introductionmentioning
confidence: 99%